2019
DOI: 10.1111/joop.12264
|View full text |Cite
|
Sign up to set email alerts
|

Gender, leadership, and the display of empathic anger

Abstract: Three experimental studies with different participant pools examined the effects of displays of empathic anger – anger that is caused by witnessing or learning of harm done to another person – on perceptions of men and women in leadership positions. In contrast to prior work, which focused on expressions of anger regarding personal failure and found double standards that favour men, the results in this study show that displays of empathic anger were significantly more beneficial for female leaders. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
0
15
0
2
Order By: Relevance
“…Similarly, Brescoll and Uhlmann (2008) found that followers tended to attribute female leaders' anger more to their personality trait (i.e., out-of-control individuals), and in turn, confer lower status to a female leader than a male leader who expresses anger. Keck (2019) found that observers tended to attribute female leaders' empathic anger to their personality trait and hence evaluated the leader as more agentic and communal, and thus more effective than male leaders who express empathic anger.…”
Section: Mediators Between Leader Anger Expression and Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Brescoll and Uhlmann (2008) found that followers tended to attribute female leaders' anger more to their personality trait (i.e., out-of-control individuals), and in turn, confer lower status to a female leader than a male leader who expresses anger. Keck (2019) found that observers tended to attribute female leaders' empathic anger to their personality trait and hence evaluated the leader as more agentic and communal, and thus more effective than male leaders who express empathic anger.…”
Section: Mediators Between Leader Anger Expression and Outcomesmentioning
confidence: 97%
“…The majority of studies used a variety of subjective indicators to evaluate leadership effectiveness as an outcome variable (Brescoll and Uhlmann, 2008, Study 2;Callister et al, 2017;Davis et al, 1992;Eberly and Fong, 2013, Study 2;Fischbach and Lichtenthaler, 2018;Glomb and Hulin, 1997;Johnson and Connelly, 2014;Keck, 2019;Lewis, 2000;Lindebaum and Fielden, 2010;Lindebaum et al, 2016;Madera and Smith, 2009;Mai-Dalton et al, 1979;Schaubroeck and Shao, 2012, Study 2;Schwarzmüller et al, 2017, Studies 2 and 3;Shao, 2019b, Study 2;Shao and Martin, 2019;Tiedens, 2001, Studies 1-2;Van Kleef et al, 2010, Preliminary Study;. These indicators include judgment of effectiveness, likelihood of promotion, conferred status, leader-member exchange (LMX) and perceived situation improvement.…”
Section: Outcomes Of Leader Anger Expressionmentioning
confidence: 99%
“…However, future research should also focus on more androgynous profiles of leaders, that is, leaders having communal and agentic traits. The modern leadership literature suggests that the ideal manager is one who can pivot between both agentic and communal behavioral and trait dimensions, and that women may have a particular advantage when it comes to displaying androgynous trait combinations (e.g., [ 66 ]). However, this literature has investigated these associations without considering organizational features such as performance [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bu yanıyla her iki duygu kişisel öfkeden ayrılmaktadır (Kişisel öfkede bireyler kendilerine ya da kişisel çıkarlarına yönelik bir haksızlık algılandıklarında öfke duymaktadırlar.) (Batson ve ark., 2007), ancak empatik öfke ahlaki öfkeden farklı olarak ahlaki bir ihlalin ardından "diğerini anlamayı" ve "soruna odaklanarak" empatik tepki verebilmeyi de içermektedir (Keck, 2019).…”
Section: Introductionunclassified
“…Görülebileceği gibi empatik öfke, olumlu ya da ahlaki toplumsal davranışların sergilenmesinde önemli bir işleve sahiptir (Hoffman, 1989(Hoffman, , 1990. Bu bilgiyi kanıtlayan çalışmalar empatik öfkenin cezalandırıcı (ahlaki normları ihlal edenlerin cezalandırılmasını isteme) (Dimitrof ve ark., 2019; Landmann ve Hess, 2017) ve onarıcı (mağdurun mağduriyetinin giderilmesini isteme) adaletin yerine getirilmesinde (van Doorn, Zeelenberg, Breugelmans, Berger ve Okimoto, 2018) ve olumlu kişilerarası ilişkilerin düzenlenmesine (Keck, 2019) kaynaklık edebildiğine işaret etmektedir.…”
Section: Introductionunclassified